2002
DOI: 10.1002/1521-3757(20020104)114:1<172::aid-ange172>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Intramolecular Oxidative Amination of Olefins through Direct Dioxygen-Coupled Palladium Catalysis

Abstract: The prominence of five-membered nitrogen-containing heterocycles in natural products and biologically active molecules [1] has prompted considerable efforts toward their synthesis. Intramolecular hydroamination [2, 3] and oxidative amination [4,5] of olefins represent powerful synthetic strategies for heterocycle formation (Scheme 1). [6] The latter isOxH 2 hydroamination oxidative amination Scheme 1. Strategies for the heterocyclization of olefinic amines or amides.particularly attractive in the context of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…These catalyst systems were only moderately successful (Table 1, entries 1–3; for full screening data, see the Supporting Information). For example, the Pd(OAc) 2 /pyridine catalyst system we originally reported for tosyl‐substituted γ‐aminoalkenes10a afforded the desired cyclic sulfamide 2 in only 39 % yield and generated the imine byproduct 3 in 25 % yield (Table 1, entry 2). In the course of testing other solvents and reaction conditions, we observed that addition of catalytic quantities of dimethyl sulfoxide improved the yield of 2 when Pd(TFA) 2 /pyridine was used as the catalyst in 1,4‐dioxane (Table 1, entries 4 and 5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These catalyst systems were only moderately successful (Table 1, entries 1–3; for full screening data, see the Supporting Information). For example, the Pd(OAc) 2 /pyridine catalyst system we originally reported for tosyl‐substituted γ‐aminoalkenes10a afforded the desired cyclic sulfamide 2 in only 39 % yield and generated the imine byproduct 3 in 25 % yield (Table 1, entry 2). In the course of testing other solvents and reaction conditions, we observed that addition of catalytic quantities of dimethyl sulfoxide improved the yield of 2 when Pd(TFA) 2 /pyridine was used as the catalyst in 1,4‐dioxane (Table 1, entries 4 and 5).…”
Section: Methodsmentioning
confidence: 99%
“…This oxidative cyclization reaction could proceed via two different mechanisms (Scheme ): aminopalladation of the alkene followed by β‐hydride elimination10a or allylic CH activation to form a π‐allyl–palladium(II) intermediate followed by CN coupling 12b,d,e. The chelating sulfoxides 4 and 5 were tested as replacements for dimethyl sulfoxide because these ligands are known to facilitate allylic CH activation;12b,d,e however, only low yields of sulfamide product 2 were obtained in these reactions (Table 1, entries 12 and 13).…”
Section: Methodsmentioning
confidence: 99%
“…Selective hydroamination of alkenyl carbamates has previously been achieved only through employment of a stoichiometric amount of Hg II followed by reduction 6. 7 Unfortunately, attempted hydroamination of carbamate 4 employing the catalyst system optimized for the hydroamination of 1 required 120 °C and formed protected pyrrolidine 5 in only 50 % yield (determined by 1 H NMR spectroscopic analysis) [Eq. (1)] 8…”
Section: Effect Of Phosphine and Solvent On The Aui‐catalyzed Hydroammentioning
confidence: 99%
“…In Zusammenhang mit der Anwendung dieses Katalysators in anderen Palladiumoxidasereaktionen (siehe Abschnitt 5.3)41 führten wir eine mechanistische Studie zur Pd(OAc) 2 /Pyridin‐katalysierten aeroben Oxidation von Benzylalkohol aus 42. Im Unterschied zur Pd(OAc) 2 /DMSO‐Reaktion – aber übereinstimmend mit anderen Palladium‐Katalysatorsystemen mit Stickstoffliganden (siehe Tabelle 1) – tritt in dieser katalytischen Reaktion ein stationärer Palladium( II )‐Zustand mit einer umsatzbegrenzenden Oxidation des Alkoholsubstrats auf.…”
Section: Alkohol‐oxidationenunclassified